The Brahmin Felon and the Wise Thief - Lubin, Timothy (Religions of South Asia, 2023)
I begin by analysing Mimamsa hermeneutics as employed in Visvarupa’s and Vijñanesvara’s commentaries on Yajñavalkya Dharmasastra 2.21, which proclaims principles for dealing with conflicts of smrti-rules, taking as an illustration the problem of self-defence against a Brahmin attacker (quoting Manava Dharmasastra 8.348–51). I then examine Bharuci’s and Medhatithi’s arguments on Manava Dharmasastra 8.314–18 (the example of the ‘wise thief’ who seeks the king’s punishment as a penance). The commentators situate the legality of the king’s interests and judicial authority in relation to Veda-based, otherworldly considerations such as sin and expiation. Punishments and penances serve different purposes, are prescribed by different authorities, and occupy distinct sections in textual sources. The case of the Brahmin felon strains the distinction: it asserts that even a Brahmin (otherwise exempt from capital punishment) may be killed if engaged in the worst crimes, but this conflicts with the rules requiring expiation for killing a Brahmin. The ‘wise thief’ is the contrived exception that proves the rule that punishment and penance are distinct; the efficacy of the act hinges on the wrong-doer’s initiative, so that the king-executioner is more instrument than agent of purification, and at his own spiritual peril. The commentators discuss these cases in terms of the relation between Dharmasastra and Arthasastra, subordinating the latter to the former.